Creating a Happy Family with Interactive Discussion Methods (Experimental Student Experience, 2023)
Family is a group of two or more people related by birth, marriage or adoption who live together; All related persons are considered as members of one family. The purpose of this community service is to create a happy family with interactive discussion methods. The community service method used is an interactive discussion method. Beginning with the delivery of family-themed materials, then disclosing household issues, and interactive discussions. Discussion is needed during the process of exploring certain topics or problems in groups. The results of the service state that it is important to do community service to families. Sometimes, from the outside we think that the family is fine, but actually the family is not well. Families that are not good have an impact on children's growth, disturbed children's growth will interfere with their mindset, disturbed mindsets will have an impact on their relationships with others, both in the neighborhood of the neighborhood community, school, office, and their families in the future if they marry. The country will be at a loss.